When Ethnologists Were Hunting for Butterflies. Anthropology and Entomology in West Africa (1928-1960) - (:unkn) unknown (My University, 2013)
At a time when fieldwork in Africa was developing in French ethnology, especially as of 1928, several comparisons were made between the human and natural sciences, specifically between ethnological surveys and entomological observations. They evinced the discipline and objectivity of anthropologists and, consequently, served to legitimate fieldwork. This strategic use of entomological metaphors can be related to the fact that, owing to their practices, ethnologists working in Africa were frequently « hunting for butterflies » : trips for collecting objects and data were also occasions for collecting insects. Between 1928 and 1960, Marcel Griaule, Michel Leiris, Germaine Dieterlen, Solange de Ganay, Jean-Paul Lebeuf, Bohumil Holas and Henri Lhote collected a large number of entomological specimens for the Museum national d’histoire naturelle and the Institut français d’Afrique noire. Little by little, insects became a part (and subject) of anthropological research. Collection practices, the identification and classification of the things collected, the production of knowledge and questions having to do with fieldwork and aesthetics underwent interferences – between ethnology and entomology – in ways that should be probed.
Keywords: African Research